FORESIGHT EDUCATION: REDEFINING LEADERSHIP FOR A BETTER FUTURE INDONESIA - Gregorius Kukuh Nugroho (Widya Mandala Surabaya Catholic University, 2020)
Problems in education are no longer simple. The challenges in the education are increasing, complex, demanding, detailed, and need to be addressed properly. Communication and technology practically change our social life. The educational system has shift from traditional learning to experiential and virtual learning (for example: online learning, google/classroom, tedex.com). It is useless to always complain about the increase funding, as an excuse to make better educational organization. Recent academic report showed, in Indonesian educational systems, there are stagnation and many resistants to transform (Prasetyawan, 2017). This is the right time to improve and to seize the opportunities to move forward. It is a time to redefine the educational system in Indonesia. It is about time to bring: real empowerment, innovations, long-term and sustainable problem solving, which in turn will create a better world. This article proposes ‘foresight’ as a method to bring a better education.